Bioactivity of Medicinal Plants and Extracts - Les, Francisco; López, Víctor; Cásedas, Guillermo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Medicinal plants and natural products have played a central role in therapeutics, being considered the origin of Pharmacy and Pharmacology. Plants are still a source in nature to obtain and isolate molecules with pharmacological applications (drug discovery), but can also be used as herbal medicinal products in traditional or complementary medicine.In addition, the WHO has launched a Traditional Medicine Strategy (2014-2023), including herbal medicines as medicinal therapies, with the aim to ensure the quality, safety, proper use, and effectiveness of traditional medicines, among other objectives.This is a reprint of articles from the Special Issue on "Bioactivity of Medicinal Plants and Extracts" published online in the open access journal Biology. This reprint includes a collection of original research and review articles on new advances in the development and application of bioactive compounds and extracts from plant matrices.